Kishenehna prima, a new genus and species of darner dragonfly (Odonata, Aeshnidae, Gomphaeschninae) from the early middle Eocene Kishenehn Formation of Montana, USA - Archibald, S. Bruce; Cannings, Robert A.; Greenwalt, Dale E. (Zootaxa, 2022)
We describe the darner dragonfly Kishenehna prima n. gen. and sp. (Odonata, Aeshnidae, Gomphaeschninae) based on a well-preserved, nearly complete female hind wing from the Lutetian Coal Creek Member of the Kishenehn Formation, northwestern Montana, USA. Kishenehna is morphologically close to the late Paleocene genus Alloaeschna Wighton & Wilson of Alberta, Canada. This is the first dragonfly (Anisoptera) described from the Kishenehn Formation and the first from the Lutetian of the Western Hemisphere.